Global solutions for a model of polymeric flows with wall slip - Baranovskii, E. S. (Mathematical methods in the applied sciences, 2017)
We consider the initial‐boundary value problem for a model of motion of aqueous polymer solutions in a bounded three‐dimensional domain subject to the Navier slip boundary condition. We construct a global (in time) weak solution to this problem. Moreover, we establish some uniqueness results, assuming additional regularity for weak solutions. Copyright © 2017 John Wiley & Sons, Ltd.